Prodrugs of Nucleoside 5'-Monophosphate Analogues: Overview of the Recent Literature Concerning their Synthesis and Applications - Roy, Béatrice; Navarro, Valentin; Peyrottes, Suzanne (Current Medicinal Chemistry, 2023)
Nucleoside analogues are widely used as anti-infectious and antitumoral agents. However, their clinical use may face limitations associated with their physicochemical properties, pharmacokinetic parameters, and/or their peculiar mechanisms of action. Indeed, once inside the cells, nucleoside analogues require to be metabolized into their corresponding (poly-)phosphorylated derivatives, mediated by cellular and/or viral kinases, in order to interfere with nucleic acid biosynthesis. Within this activation process, the first-phosphorylation step is often the limiting one and to overcome this limitation, numerous prodrug approaches have been proposed. Herein, we will focus on recent literature data (from 2015 and onwards) related to new prodrug strategies, the development of original synthetic approaches and novel applications of nucleotide prodrugs (namely pronucleotides) leading to the intracellular delivery of 5’-monophosphate nucleoside analogues.
Keywords: Pronucleotide